2012
DOI: 10.1021/cg200981d
|View full text |Cite
|
Sign up to set email alerts
|

Seed-Induced, Structure Directing Agent-Free Crystallization of Sub-Micrometer Zeolite ZSM-5: A Population Balance Analysis

Abstract: Crystallization of sub-micrometer sized zeolite ZSM-5 from a TPA-free (TPA = tetrapropyl ammonium) reaction mixture 1.0Al 2 O 3 /100SiO 2 /28Na 2 O/4000H 2 O, seeded with silicalite-1 seed crystals of two different sizes (260 and 690 nm), was analyzed by population balance methodology. Changes in crystal size distributions and fractions of the newly formed crystalline phase (ZSM-5) were measured and compared with the calculated (simulated) data. For the crystalline end products having D ≥ 0.5 μm (D is the equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…9,10 However, the organic templates needed for the synthesis are toxic and highly expensive as well as these organic species enclosed within zeolitic structures can be removed by calcination at high temperatures; this inevitably leads to both energy consumption and environmental pollution. 11,12 Therefore, organic template-free synthesis of zeolites is strongly desirable since it is more ideal, cheaper, and less toxic. 13,14 Silica is the second most abundant element on the earth surface, which accounts for approximately 32% of the total weight of it.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, the organic templates needed for the synthesis are toxic and highly expensive as well as these organic species enclosed within zeolitic structures can be removed by calcination at high temperatures; this inevitably leads to both energy consumption and environmental pollution. 11,12 Therefore, organic template-free synthesis of zeolites is strongly desirable since it is more ideal, cheaper, and less toxic. 13,14 Silica is the second most abundant element on the earth surface, which accounts for approximately 32% of the total weight of it.…”
Section: Introductionmentioning
confidence: 99%
“…Based on seed surface crystallization mechanism, N. Ren et al proposed a method for facile, rapid, controllable and low-cost synthesis of ZSM-5 zeolite with submicron-size. [40][41][42][43] Furthermore, crystal growth kinetics, crystalline yield, and physicochemical properties of zeolite nanoparticles as a function of the seed concentration and synthesis temperature were addressed by V. Valtchev et al 44 However, most reports focused on the study of the seed role under a single system. Few studies have revealed the effect of the synthesis system on the particle size of ZSM-5 in the presence of seed crystals.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The PBE have been applied for estimating and modeling various crystallization systems. 11,12,[21][22][23][24] However, PBE containing breakage and agglomeration terms, which are commonly expressed as integral functions, are so complex that analytic solution of the PBE could not be obtained. 18 Although solutions of the PBE could be obtained by several numerical methods, such as the method of moments, 25,26 the method of characteristics, 27 discretized population balances, [28][29][30] and weighted residuals, 31 the computation time for model solving is significantly long and it is too difficult to estimate the parameters required for expressing the breakage and agglomeration phenomena.…”
Section: Introductionmentioning
confidence: 99%